DEVELOPING LISTENING AND SPEAKING SKILLS THROUGH INTERACTIVE CLASSROOM ACTIVITIES IN PRIMARY ENGLISH LESSONS - Jovliyeva Nafosat Bahodir qizi (НАУЧНЫЕ ИССЛЕДОВАНИЯ И ИННОВАЦИИ, 2025)
Annotation: This article discusses the importance of interactive classroom activities in improving primary students’ listening and speaking skills in English. It examines how games, pair work, role plays, and multimedia tools enhance communication, motivation, and confidence among young learners. The paper highlights the teacher’s role in organizing meaningful interaction and provides examples of effective classroom techniques for developing oral skills.